Meta-analysis of the amino acid digestibility of oilseed meal in growing pigs. (3rd May 2016) - Messad, F.; Létourneau-Montminy, M. P.; Charbonneau, E.; Sauvant, D.; Guay, F.
Abstract : Oilseed meal is an important source of essential amino acids (EAA) for livestock production. It is the second most important ingredient in pig feed after grains. Optimal use of these ingredients requires precise knowledge of amino acid standardized ileal digestibility (SID), which may vary depending on several factors including botanical variety or processing treatments. A meta-analysis was performed in order to derive models for predicting the SID of soybean, cotton and rapeseed meal EAA, based on chemical composition data such as CP, total concentration of each EAA and fibre (crude fibre, ADF and NDF) content. A database of 47 references (224 experimental treatments) was built. A model incorporating processing method of the meals (e.g. cold pressed, expeller pressed, solvent extracted), experimental surgical procedure (T-cannula, re-entrant cannula, post valve T-cannula and ileo-rectal anastomosis) and pig growth stage (BW⩽ or ⩾25 kg) was tested. Results indicated that neither processing nor BW affected EAA SID. NDF was the best predictor of SID ( R 2 =0.944, 0.836, 0.779, 0.899 and 0.814, respectively, for Lys, Met, Thr, Trp and Val). The total EAA content was the best predictor of digestible content (g/kg diet) for each EAA ( R 2 =0.990, 0.985, 0.977, 0.985 and 0.978, respectively, for Lys, Met, Thr, Trp and Val). This study shows that routine chemical analyses may be used to predict EAA digestibility with satisfactory accuracy.